Pharmacotherapy Treatment Patterns, Outcomes, and Health Resource Utilization Among Patients with Heart Failure with Reduced Ejection Fraction at a U.S. Academic Medical Center. Issue 2 (3rd February 2016) - Bress, Adam P.; King, Jordan B.; Brixner, Diana; Kielhorn, Adrian; Patel, Harshali K.; Maya, Juan; Lee, Vinson C.; Biskupiak, Joseph; Munger, Mark
Abstract : Study Objective: To assess clinical characteristics, pharmacotherapy treatment patterns, resource utilization and associated charges, and morbidity and mortality outcomes among a real‐world cohort of patients with heart failure with reduced ejection fraction (HFrEF) in an academic medical center setting. Design: Retrospective analysis. Data Source: Electronic health record database that includes clinical, laboratory, and administrative data for all facilities of the University of Utah Health Care System. Patients: A total of 989 adults with prevalent (preexisting) HFrEF, identified by using the International Classification of Diseases, Ninth Revision, Clinical Modification code 428.x (heart failure) between January 1, 2007, and June 30, 2013, and who had a left ventricular ejection fraction of 40% or lower. Measurements and Main Results: The cohort had a mean age of 64 ± 15 years and was predominantly white (71%) and male (74%). Patients received β‐blockers, angiotensin‐converting enzyme inhibitors (ACEIs) or angiotensin II receptor blockers (ARBs), and aldosterone receptor antagonists (ARAs) at rates of 79%, 69%, and 29%, respectively. Patients achieved target doses of β‐blockers, ACEIs, and ARBs at rates of only 24%, 31%, and 13%, respectively. Overall, 58% of patients were prescribed dual therapy with a β‐blocker and an ACEI or ARB, and 19% were prescribed triple therapy (β‐blocker, an ACEI or ARB, and an ARA). Univariate and multivariate logistic regression models were used to assess the association between baseline characteristics with the presence of triple therapy. Two variables were statistically significant in both models: increasing age was associated with a lower odds of triple therapy (univariate: odds ratio [OR] 0.760, 95% confidence interval [CI] 0.673–0.857; multivariate: OR 0.768, 95% CI 0.625–0.942), whereas receipt of an implantable cardiac device was associated with a 2‐fold increase in the odds of triple therapy (univariate: OR 2.1, 95% CI 1.4–3.1; multivariate: OR 2.1, 95% CI 1.3–3.5). During a mean ± SD follow‐up of 36 ± 27 months, all‐cause mortality was 0.12 per person‐year. There were 1311 all‐cause hospitalizations of which 611 (47%) were for worsening heart failure. The rate of all‐cause and heart failure–specific hospitalizations was 0.44 and 0.21 per person‐year of follow‐up, respectively. The median length of stay was 6.4 ± 8.8 days, and the median charge was 22, 310. The 30‐day all‐cause readmission rate was 20%, and the primary reason for readmission was heart failure in 65% of cases. Conclusion: This study demonstrates the continuing significant disease and economic burden for patients with HFrEF. Challenges remain in utilization of established disease‐modifying therapy and in the treatment of patients with HFrEF and multiple comorbidities.